Evaluating a Natural-Based Solution for Its Stimulation in Cucumis sativus Plants and Fruits - Chrysargyris, Antonios; Xylia, Panayiota; Stavrinides, Menelaos; Tzortzakis, Nikos G. (My University, 2025)
The current study researched the biostimulant impacts of a natural-based solution (NBS) that contained eucalyptus and rosemary essential oils on cucumber crops. The effects of NBS (one time-NBS1; two times-NBS2) application on plant development and physiological attributes (chlorophylls, stomatal conductance), total phenolics, non-enzymatic and enzymatic antioxidant activities, leaf minerals content, cucumber quality attributes at harvest and after one-week storage were assessed through experiments. NBS1 spraying was less effective than NBS2 application because it resulted in a decrease in mineral accumulation (like reduced nitrogen) and other physiological characteristics (like chlorophylls). The plants’ enhanced oxidative stress and activation of several enzymatic antioxidant systems were reflected in the use of a commercial solution (CS) based on amino acids and biostimulants, which also boosted stomatal conductance, reduced nitrogen, calcium, and magnesium accumulation, and antioxidant capacity. No differences were found in plant height, number of leaves, plant biomass, chlorophyll fluorescence, total phenols, and various fruit quality attributes, including firmness, fresh weight, respiration rates, total soluble solids, ascorbic acid, decay, and marketability among the treatments. In fact, the effects of both CS and NBS treatment on cucumber plants and fruits were less pronounced, suggesting that more than two applications should be explored in the future.
Keywords: biostimulants; cucumber; essential oils; Eucalyptus crabraL; fruit quality; Rosmarinus officinalisL